(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda literatures include the descriptions of many drugs in terms of their names, properties and therapeutic usage. But there are many drugs, despite their medicinal value and wide usage among ethnic groups, left unrecorded in the classical texts. These drugs are generally termed as Anukta dravya. Action of Anukta dravya can be explained with its rasapanchaka viz. Rasa (taste), Guna (quality), Veerya (potency), Vipaka (transformation) and Prabhava (special action). Among these attributes of a drug, Rasa is the only parameter which can be assessed by direct perception. Cissus latifolia Lam. is an extra-pharmacopoeial drug with several ethnomedicinal claims. So the Rasa analysis of Cissus latifolia Lam. was done in 30 volunteers using a structured questionnaire. On analysing the data, it was found to have Kashaya rasa (astringent) and Tikta anurasa (bitter).